An analysis and comparison of two German thrust-fencing manuscripts - Reinier van Noort; Jan Schäfer (Bern Open Publishing, 2017)
In this contribution, we will discuss two German fencing manuscripts - Mscr.Dresd.C.13 (SLUB Dresden) and Add MS 17533 (BL London). Both manuscripts present texts on thrust-fencing based on the teachings of Salvator Fabris. The dedication of manuscript C13 was signed by the famous fencing author Johann Georg Pascha. The author of one of the texts contained in the 17533 manuscript is named H.A.V.. A textual analysis has been performed on these two books, and then the contents of the works have been compared. This comparison shows that C13 presents a largely identical text to the main treatises contained in 17533, the most significant difference being certain additions in C13, which Pascha also discusses in his dedication. Based on our analysis, both C13 and 17533 appear to present copies of an original text. We further hypothesize that H.A.V., the author of this original text, was Heinrich von und zum Velde, the fencing master of Johann Joachim Hynitzsch.